Computational simulation of heat transfer in a flow around a tube banks using fluent / Irfah Ismail - Ismail, Irfah (2005)
Two-dimensional of simulation modelling of heat transfer in an incompressible fluid flow around the tube banks had been conducted. This study is about computational simulation of heat transfer around the tube banks by using FLUENT. The result for in-line and staggered cases for the maximum velocity, temperature distribution and the flow pattern are discuss.